A Post-Work Approach to Influencer Labor: The Paradox of Sustainability Influencers - Rachel Wood (Social Media + Society)
How do Instagram sustainability influencers communicate criticisms of consumer culture, and try to promote more sustainable alternatives, in the context of a platform and industry that seeks to promote consumption by design? Drawing on an ethnography of Instagram influencers who advocate “zero waste” lifestyle politics, this paper argues that a “sustainability paradox” emerges from the impossibility of aligning environmental values with the commercial norms of the influencer industry. This paradox necessitates continuous negotiation and management for influencers, and routinely excludes them from pathways to paid work. As extensive research on influencer labor has shown, sustainability influencers are far from alone in being systematically marginalized from paid work because they are not “advertiser friendly” or “brand safe” according to the capitalist norms of social media platforms and the influencer industry. The paper makes two key arguments regarding the causes of, and solutions to, this problem. First, the “paradox” faced by sustainability influencers points to the irreparable unsustainability of the influencer industry and the environmentally destructive systems of production, promotion and consumption which it exists to promote. And second, solutions to the systemic problems of exploitative influencer labor cannot be found from tweaks to labor conditions in this unsustainable industry. Instead, the paper makes a case for the value of a “post-work” approach to influencer labor, which broadens critical and political imaginaries for what “influencing” might mean outside of exclusionary and environmentally catastrophic hegemonies of promotional labor and consumption.